ANALISIS SISTEM KINERJA PELAYANAN AIR MINUM DALAM UPAYA PENINGKATAN KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA SAMARINDA STUDI KASUS INSTALASI PENGOLAHAN AIR BERSIH (IPA) UNIT 3 SAMARINDA SEBERANG - ISMAYA, DEDY (KURVA S JURNAL MAHASISWA, 2014)
Water is a primary need for daily human life, therefore the provision of clean water for rural and urban population is absolutely necessary. Regional Water Company (PDAM) has a very important role in providing clean water as a basic necessity of life that meets the requirements, both in terms of aspects of quality, quantity and continuity.                    Water Treatment Plant (IPA) Unit 3 Samarinda Seberang at PDAM Samarinda with a production capacity of 125 liters / sec is currently serving a population of Samarinda Seberang as many as 15 577 households where the need for compliance with the use of drinking water is also increasing, was not able to serve the needs of clean water society and the means of social infrastructure, so that distribution is currently done pengiliran strategic measures and efficient and good management system, including for the needs of 10 (ten) years into the future, so that the needs of the community and the public as well as the smooth development can be met and there is no occur sharing.                From the analysis and calculations as well as the discussion on this research, the projected service levels IPA Unit 3 Samarinda Seberang the next ten years (2015-2024) for conditions of service of its growth rate of 4.66% / year, water production growth rate 9.18% / year , water distribution growth rate of 7.72% / year, water sales revenue growth rate of 6.20% / year, operating expenses growth rate of 5.25% / year, profit in 2015 amounted to Rp. 1,715,185,389.00, and Profit 2024: Rp. 5,042,130,458.00. System Performance IPA Unit 3 Samarinda Seberang on the position of Growth / Aggressive (quadrant I), and implement strategies to optimize internal expansion, consistently implement programs for the development of performance IPA Unit 3 Samarinda Seberang accordance with priorities, and improve the quality of Human Resources (SDM) IPA Unit 3 Samarinda Seberang continuously and tiered with attention to employee career advancement and respect for employees